Structural, spectroscopic, dielectric, and magnetic properties of Fe/Cu co-doped hydroxyapatites prepared by a wet-chemical method - Ercan, Ismail; Kaygili, Omer; Kayed, Tarek; Bulut, Niyazi; Tombuloglu, Huseyin; Ince, Turan; Ercan, Filiz (Elsevier, 2022)
In this study, the effects of Cu and Fe additives on the structural, dielectric, magnetic, thermal and morphology of hydroxyapatite (HAp) samples were investigated and reported in detail for the first time. The prepared systems were also modeled and examined theoretically. It can be said that both additives affect the thermal behavior of the HAp structure. The addition of Cu affected the morphology of submicron-sized particles with spherical-like shapes with a low degree of agglomeration. Diffuse reflection data revealed that the energy band gap values decreased as Cu was added to the Fe-based HAp structure. The dielectric constant (epsilon') had high values at low frequencies in all samples and decreased with increasing frequency. It could be concluded that Fe/Cu incorporation to hydroxyapatites enhanced its thermal, magnetic, and dielectric properties required for mimicking natural HAps to open a successful venue for medical application in the healing regeneration of bone.
Keywords: Hydroxyapatite; Dielectric properties; Magnetic properties